The EU-Tunisia Deep and Comprehensive Free Trade Area (DCFTA): Macroeconomic impacts and pro-developmental policy responses - Bernhard Tröster; Werner Raza; Hannes Grohs; Jan Grumiller; Cornelia Staritz; Rudi von Arnim (Austrian Foundation for Development Research (ÖFSE), 2018)
The European Union (EU) and Tunisia launched negotiations on a Deep and Comprehensive Free Trade Area (DCFTA) in 2015. So far, progress has been limited. The enhanced integration of the Tunisian economy into the EU single market involves several controversial topics. Above and beyond the elimination of tariffs in sensitive agricultural sectors, these concern in particular the liberalization of trade in services, investment and public procurement. At the same time, the negotiations take place under challenging economic, political and social circumstances within the country and the MENA region, which call for a particularly prudent approach. Our assessment of expected economic impacts points to negative GDP effects and minor employment effects in Tunisia in the short to medium term in the case of full tariff liberalization and extensive harmonisation of the regulatory frameworks. Therefore, in the negotiations, the EU should prioritize short-term benefits for the Tunisian economy, mitigate adjustments costs and pro-actively support productive development and upgrading.
Keywords: 330